Two-way predation between immature stages of the hoverfly Eupeodes corollae and the invasive fall armyworm (Spodoptera frugiperda J. E. Smith) - Hui LI; Shan-shan JIANG; Hao-wen ZHANG; Ting GENG; Kris A.G. WYCKHUYS; Kong-ming WU (Journal of Integrative Agriculture, 2021)
Since its 2018 invasion of eastern Asia, the fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) has become a key pest in local maize production. Though pesticides have been widely used to mitigate the initial S. frugiperda attack, biological control is receiving ample attention as a desirable, environmentally-sound alternative to chemical control. Hoverflies (Diptera: Syrphidae) are abundant natural enemies in Chinese maize fields and have been observed to consume S. frugiperda larvae. In this study, we use laboratory assays to study the two-way interaction between immature stages of S. frugiperda and the endemic syrphid Eupeodes corollae. To mimic natural conditions, assays were performed in the presence of fresh maize leaves. Those 2nd or 3rd instar larvae of E. corollae preyed on 1st and 2nd instar S. frugiperda larvae with a Holling type III response, consuming a respective theoretical maximum of 43.48 and 83.33 larvae over a 24-h period. Conversely, once S. frugiperda larvae reached 3rd instar, they exhibited aggressive behavior and equally preyed on syrphid larvae with a Holling type III response. Those 5th and 6th instar larvae of S. frugiperda consumed a respective 16.39–19.23, 6.02–19.61 and 6.76–8.26 of 1st, 2nd and 3rd instar E. corollae larvae per day. Though our results await field-level validation, S. frugiperda agonistic (i.e., defensive) and consumptive behavior towards resident natural enemies such as E. corollae possibly degrades biotic resistance and raises its invasion potential. Our findings shine new light on the interaction between lepidopteran herbivores and their natural enemies, and can help advance the development of conservation biological control and other integrated pest management (IPM) strategies against S. frugiperda in China and abroad.